A Soft and Robust Spring Based Triboelectric Nanogenerator for Harvesting Arbitrary Directional Vibration Energy and Self‐Powered Vibration Sensing. Issue 9 (18th December 2017) - Xu, Minyi; Wang, Peihong; Wang, Yi‐Cheng; Zhang, Steven L.; Wang, Aurelia Chi; Zhang, Chunli; Wang, Zhengjun; Pan, Xinxiang; Wang, Zhong Lin
Abstract: Vibration is a common mechanical phenomenon and possesses mechanical energy in ambient environment, which can serve as a sustainable source of power for equipment and devices if it can be effectively collected. In the present work, a novel soft and robust triboelectric nanogenerator (TENG) made of a silicone rubber‐spring helical structure with nanocomposite‐based elastomeric electrodes is proposed. Such a spring based TENG (S‐TENG) structure operates in the contact‐separation mode upon vibrating and can effectively convert mechanical energy from ambient excitation into electrical energy. The two fundamental vibration modes resulting from the vertical and horizontal excitation are analyzed theoretically, numerically, and experimentally. Under the resonant states of the S‐TENG, its peak power density is found to be 240 and 45 mW m −2 with an external load of 10 MΩ and an acceleration amplitude of 23 m s −2 . Additionally, the dependence of the S‐TENG's output signal on the ambient excitation can be used as a prime self‐powered active vibration sensor that can be applied to monitor the acceleration and frequency of the ambient excitation. Therefore, the newly designed S‐TENG has a great potential in harvesting arbitrary directional vibration energy and serving as a self‐powered vibration sensor. Abstract : A novel soft and robust triboelectric nanogenerator (TENG) made of a silicone rubber‐spring helical structure with nanocomposite based elastomeric electrodes is designed . Such a spring based TENG structure operates in contact‐separation mode upon vibrating and can effectively convert mechanical energy from arbitrary direction excitation into electrical energy. It can also serve as a self‐powered sensor for vibration monitoring.